Long-term probucol therapy continues to suppress markers of neurovascular inflammation in a dietary induced model of cerebral capillary dysfunction - Takechi, Ryu; Pallebage-Gamarallage, Menuka; Lam, Virginie; Giles, Corey; Mamo, John (BioMed Central Ltd., 2014)
Background: Probucol has been shown to prevent cerebral capillary disturbances characterized by blood-to-brain extravasation of plasma derived proteins and neurovascular inflammation in mice maintained on western-styled diets for 12 weeks. However the effect of probucol on capillary integrity in aging models with capillary dysfunction is not known. Methods: Wild-type C57BL6 mice were randomized to a low-fat (LF); saturated-fat (SFA); or SFA + Probucol diet for up to12 months of intervention. Results: Mice fed the LF diet had substantially greater parenchymal abundance of plasma derived IgG and apo B lipoproteins at 12 months, compared to LF mice at 3 months of intervention. Markers of neurovascular inflammation were also greater at 12 months in LF fed mice compared to LF mice at 3 months. The SFA diet exacerbated the aging induced parenchymal abundance of IgG and of apo B lipoproteins and neurovascular inflammation at 12 months. The SFA effects were associated with increased production of intestinal lipoprotein amyloid-ß (Aß). The co-provision of probucol with the SFA completely abolished heightened inflammation at 12 months. Probucol attenuated SFA-induced capillary permeability but had only a modest inhibitory effect on parenchymal retention of apoB lipoproteins. The improvements in markers of inflammation and capillary integrity because of probucol correlated with enterocytic genesis of chylomicron Aß. Conclusion: In this long-term feeding study, probucol profoundly suppressed dietary SFA induced disturbances in capillary integrity but had a more modest effect on age-associated changes.